2018
DOI: 10.1016/j.jdiacomp.2018.08.003
|View full text |Cite|
|
Sign up to set email alerts
|

Glycemic reduction alters white blood cell counts and inflammatory gene expression in diabetes

Abstract: Significant glycemic reduction in subjects with poorly controlled diabetes led to reduced circulating WBC counts and inflammatory gene expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 49 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…In this regard, chronic inflammation due mainly to the activation of the myeloid cell lineage (e.g., macrophages and neutrophils), is directly related to the induction of IR ( 4 , 122 ). Fang et al have shown that patients with T2DM have elevated numbers of circulating leukocytes that express high levels of inflammatory gene products but glycemic control can reverse the situation ( 123 ). De Souza Prestes et al have indicated that exposure of leukocytes to MGO changes their morphology by making them larger and more granular, increases their ability to produce ROS and decreases their expression of antioxidant genes ( 124 ).…”
Section: Effects Of T2dm On the Immune Systemmentioning
confidence: 99%
“…In this regard, chronic inflammation due mainly to the activation of the myeloid cell lineage (e.g., macrophages and neutrophils), is directly related to the induction of IR ( 4 , 122 ). Fang et al have shown that patients with T2DM have elevated numbers of circulating leukocytes that express high levels of inflammatory gene products but glycemic control can reverse the situation ( 123 ). De Souza Prestes et al have indicated that exposure of leukocytes to MGO changes their morphology by making them larger and more granular, increases their ability to produce ROS and decreases their expression of antioxidant genes ( 124 ).…”
Section: Effects Of T2dm On the Immune Systemmentioning
confidence: 99%
“…This threshold of 2.0 mM glucose is much lower than acceptable blood glucose levels, suggesting that there are other factors which maintain endothelial cell health in normoglycemia in vivo , i.e., up to 5.5mM/L. Indeed, there are damage limitation factors in the circulation which protect the endothelium, such as acute phase reactants ( 29 – 31 ) and circulating antiproteases ( 32 , 33 ), while the number and activation status of the circulating cells in the hyperglycemic milieu must also have an effect ( 24 , 34 ).…”
Section: What Triggers the Development Of Complications In Diabetes?mentioning
confidence: 99%
“…Extracellular ROS production, pro-inflammatory cytokine release and NET formation are increased in diabetes, whereas neutrophil migration, apoptosis and intracellular ROS production are reduced, which ultimately impairs bacterial killing and inflammation ( 56 , 58 61 ). Phenotypic variations in neutrophil function are supported by transcriptomic data, showcasing a fundamentally altered profile in key pro-inflammatory genes in neutrophils in PWD ( 62 , 63 ).…”
Section: Introductionmentioning
confidence: 96%